PENGARUH BUDAYA ORGANISASI TERHADAP KUALITAS PELAYANAN KEBIDANAN DI RUMAH SAKIT - Ria Lusi Utami; Winda Febriani; Nita Berliana Br Ginting (Politeknik Ganesha Medan, 2022)
The quality of midwifery care is a crucial factor in ensuring maternal and infant health, as well as a positive birth experience. In hospitals, this quality of care is not only determined by the competence of individual midwives but is also strongly influenced by the prevailing organizational culture. Organizational culture shapes the values, norms, beliefs, and behaviors shared by members of the organization. This literature review aims to analyze and synthesize how various dimensions of organizational culture (e.g., patient-centered culture, safety culture, innovation culture, and support culture) influence the quality of midwifery care in hospital settings. The review results indicate that a strong, positive, and quality-oriented organizational culture significantly improves midwife job satisfaction, team collaboration, adherence to standards, and ultimately, the quality of care received by patients. Conversely, a dysfunctional culture can hinder midwife performance and compromise patient safety. The implications of this review highlight the importance of leadership in shaping a culture that supports excellence in midwifery care.